EFEKTIVITAS PEMBELAJARAN DARING DI MASA PENDEMI COVID-19 PADA MAHASISWA PRODI PPKn FKIP UNRAM - Ismail, M; Kurniawansyah, Edy; Fauzan, Ahmad; Basariah, Basariah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
This study aims to determine the effectiveness of online learning during the COVID-19 pandemic for students of the PPKn FKIP UNRAM Study Program. This research was carried out in the PPKn FKIP Unram study program. The method used in this study is to use a qualitative approach to reveal symptoms or phenomena related to the effectiveness of online learning during the COVID-19 pandemic for students of the PPKn FKIP UNRAM Study Program. The data collection technique is using a questionnaire that contains the types of questions that are distributed using the google form. The data analysis technique is carried out with the data reduction stage, the data display stage and the conclusion drawing and verification stage. The results showed that the process of implementing teaching and learning activities in the PPKn FKIP Unram study program ran smoothly and was very effective.